Gastric protection by alpha-melanocyte-stimulating hormone against ethanol in rats: Involvement of somatostatin - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The proopiomelanocortin-derived tridecapeptide alpha-melanocyte-stimulating hormone (alpha-MSH) is a neuropeptide that exerts broad anti-inflammatory actions in mammals. This study aimed to investigate the effect of alpha-MSH on ethanol-induced gastric ulcer in rats and to evaluate the involvement of endogenous somatostatin in the actions of the peptide. The rats received 1 mL 75% ethanol or saline orally. alpha-MSH was given (25 mu g/rat, i.p.) alone or following the somatostatin antagonist cyclo-(7-aminoheptanoyl-PH-E-D-Ttp-Lys-THR) (10 mu M/kg; i.p.) administration. Gastric lesions were scored macroscopically and microscopically following decapitation at 30 min after ethanol challenge. Gastric malondialdehyde (MDA) level, myeloperoxidase (MPO) activity and mast cell counts were assessed. Ethanol-induced gastric hemorrhagic lesions were characterized by increased gastric MDA level, MPO activity and mast cell counts. alpha-MSH treatment decreased the extent of tissue injury and reversed tissue MDA level, MPO activity and mast cell counts. The effect of the peptide on the severity of gastric lesions, MDA level and MPO activity was reversed by the somatostatin antagonist. In conclusion, alpha-MSH is beneficial in a rat model of gastric ulcer via mechanisms which partly involve the endogenous somatostatin. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: alpha-melanocyte-stimulating hormone; somatostatin; gastric ulcer; ethanol; rat; MUCOSAL INJURY; LIPID-PEROXIDATION; NITRIC-OXIDE; MAST-CELLS; DAMAGE; INFLAMMATION; MODULATION; MSH; MECHANISMS